(untitled) (Research, Society and Development, 2020)
This work aimed to analyze in the knowledge production the factors that influence the prevention and control of infection of the surgical site in patients undergoing cardiac surgery and the role of nursing. This is an integrative review study. The following databases were used for selection: MEDLINE; LILACS; IBECS; BDENF; SCIELO; and the service of the U. S. National Library of Medicine (NLM): PubMed, according to the PICO guiding criteria; descriptors and synonym pertinent to the theme identified through the DECs and MeSH: surgical wound infection, cardiac surgery, nursing, in portuguese, english and spanish. The inclusion criteria were: articles made available in full, in the selected databases, which adhere to the theme in Portuguese, Spanish and English, published between 2009 and 2019. The results included 05 national and international articles with different approaches methodological and investigative contexts, published between the years 2016 to 2018. In view of the above, it is concluded that the assessment of risk factors for the occurrence of surgical site infection in patients undergoing cardiac surgery is essential for health care and that the planning of care strategies and that nursing actions with patients undergoing cardiac surgery favor patient safety.